If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -6(x + 5) = 4 Reorder the terms: 4 + -6(5 + x) = 4 4 + (5 * -6 + x * -6) = 4 4 + (-30 + -6x) = 4 Combine like terms: 4 + -30 = -26 -26 + -6x = 4 Solving -26 + -6x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + -6x = 4 + 26 Combine like terms: -26 + 26 = 0 0 + -6x = 4 + 26 -6x = 4 + 26 Combine like terms: 4 + 26 = 30 -6x = 30 Divide each side by '-6'. x = -5 Simplifying x = -5
| 4d+2(d+3)=-3(d-2) | | m+m+1+m+2=57 | | 5x+3=21-4x | | 4-8x=24-4x | | x/2+14=46 | | 9x-4=5x+7 | | 8n-1=5n-10 | | 69*2-x=45 | | 6x+3=91-5x | | 10+2x=15+3x | | 86-5x=13x+16 | | z^4-8z+15=0 | | 14+5x=22+6x | | 3*3+4=16 | | p^2-13p+18=0 | | 5x-3=11x-4 | | 1-9x=55-3x | | 5x-4y=-28 | | 5x+23=10x-67 | | 5x+23=10x-68 | | 75-3x=10x-4x | | z^4-8z^2+15=0 | | 6x+12.3-10.2=1.5 | | Z-y-b= | | -p-1=-21 | | (K-p)*(r-j)= | | 3x^2-6x=x^2+x | | z+4=-4 | | m-8=-5 | | z+6=-6 | | z-7=3 | | z-7=0 |